Tetrahydrobiopterin responsiveness in phenylketonuria: prediction with the 48-hour loading test and genotype - Anjema, Karen; van Rijn, Margreet; Hofstede, Floris C.; Bosch, Annet M.; Hollak, Carla EM; Rubio-Gozalbo, Estela; de Vries, Maaike C.; Janssen, Mirian CH; Boelen, Carolien CA; Burgerhof, Johannes GM; Blau, Nenad; Heiner-Fokkema, M. Rebecca; et al. (Orphanet journal of rare diseases, 2013)
How to efficiently diagnose tetrahydrobiopterin (BH4) responsiveness in patients with phenylketonuria remains unclear. This study investigated the positive predictive value (PPV) of the 48-hour BH4 loading test and the additional value of genotype.
Gesehen am 25.11.2020